2015
DOI: 10.1038/bmt.2015.16
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota trajectory in pediatric patients undergoing hematopoietic SCT

Abstract: Acute GvHD (aGvHD) is the main complication of hematopoietic SCT (HSCT) during the treatment of hematological disorders. We carried out the first longitudinal study to follow the gut microbiota trajectory, from both the phylogenetic and functional points of view, in pediatric patients undergoing HSCT. Gut microbiota trajectories and short-chain fatty acid production profiles were followed starting from before HSCT and through the 3-4 months after transplant in children developing and not developing aGvHD. Acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
148
4
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(167 citation statements)
references
References 43 publications
13
148
4
2
Order By: Relevance
“…Temporal microbiota dynamics thus seemed to be linked to the gut condition of the patient. Beneficial bacteria such as Bacteroides, 5 Lactobacillus, 8 Bifidobacterium, and Faecalibacterium 14 were dominant in cases 1 to 3, 15 whereas Escherichia, which has been strongly correlated with GVHD in a mouse model, 9 was increased at the recurrence of aGVHD in case 4. The number of operational taxonomic units and diversity of the intestinal microbiota did not fully recover after FMT, even with apparent clinical response (supplemental Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Temporal microbiota dynamics thus seemed to be linked to the gut condition of the patient. Beneficial bacteria such as Bacteroides, 5 Lactobacillus, 8 Bifidobacterium, and Faecalibacterium 14 were dominant in cases 1 to 3, 15 whereas Escherichia, which has been strongly correlated with GVHD in a mouse model, 9 was increased at the recurrence of aGVHD in case 4. The number of operational taxonomic units and diversity of the intestinal microbiota did not fully recover after FMT, even with apparent clinical response (supplemental Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the intestinal microbiota has been reported to be associated with the entire spectrum of aGVHD. 4,5,10 In summary, FMT was safely performed in SCT patients and offers promise as a potential treatment option for aGVHD. Further evaluation to confirm the safety and efficacy of FMT for aGVHD is warranted.…”
Section: Aes (Grade)mentioning
confidence: 99%
See 1 more Smart Citation
“…78 A longitudinal study of pediatric patients undergoing HCT showed that it often takes over 2 months after transplantation to regain intestinal diversity. 79 Lost diversity and intestinal domination of opportunistic bacteria have also been shown to precede blood stream infection (BSI) by the same pathogen in HCT patients. 55,80 As such, some investigators are exploring alternative antibiotic prophylactic strategies that may better preserve patient flora and maintain gut homeostasis.…”
Section: Diversity Loss Gvhd and Posttransplant Infectionsmentioning
confidence: 99%
“…The decrease in diversity following allo-HSCT is often accompanied by the expansion of a single taxon. In most cases, at the onset of GvHD, an increase in the abundance of the members of the genus Enterococcus has been observed [17, 19]. This is frequently followed by BSI with vancomycin-resistant Enterococci and a decrease in the abundance of members of the order Clostridiales including Faecalibacterium spp.…”
Section: Allogenic Hematopoietic Stem Cell Transplantation and Gvhdmentioning
confidence: 99%